Radiative Cooling Technology and Fundamental Analysis Review - M. Benlattar (Recent Progress in Science and Technology Vol. 9, 2023)
Passive daytime or nighttime radiative cooling as a emerging technology shows good potential for both saving the building energy and maximizing the efficiency of solar cell modules. Particularly, the passive radiative cooling in the PV radiative field is attracting extensive attention than the other traditional cooling methods. To this end, we propose a double layer coating shield that should be designed to have both a high transparency in the solar range and high emissivity in the atmospheric window to improve heat dissipation capacity of solar cell modules. This chapter highlights the potential of porous TiO2/BK7 system as widely available shield for passive radiative cooling in glass packaging PV field.